Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Umkm Seblak Cinderella Rawajaya - M. Rio Saputra; Siti Lutfyah; Deka Susanti; Nuraini Nuraini; Wulan Oktarina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the digital marketing strategies implemented by Seblak Cinderella MSME and their impact on increasing product sales. The research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving the business owner and customers as research informants. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that Seblak Cinderella utilizes various promotional media, including Instagram, TikTok, WhatsApp, banners, and promotional discounts as part of its marketing strategy. The use of digital media is carried out through the creation of attractive content, regular dissemination of product information, and active interaction with customers. These strategies have positively contributed to sales growth, as indicated by an increase in the number of customers, higher consumer purchase interest, broader market reach, and stronger business visibility amid competition in the culinary industry. This study demonstrates that the combination of social media utilization, direct promotion, and discount programs can serve as an effective strategy for MSMEs to enhance competitiveness and business sustainability in the digital era.